PENGARUH KEPEMIMPINAN MANAGER TERHADAP KINERJA KARYAWAN FOOD AND BAVARAGE DI KYRIAD HOTEL BUMIMINANG PADANG - Faruqi, Ahmad (RC-INSTITUT, 2019)
This study aims to determine the effect of the Leadership Manager on food and bavarage employee performance di at Kyriad Hotel Bumiminang Padang. This type of research is causal associative research using simple linear regression analysis. The population in this study were employees who were 30 people and the number of samples in this study amounted to 30 employees except the head of department with sampling techniques were saturated samples. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. Technical analysis uses the help of the SPSS Computer Program version 16.00. The results showed: (1) Leadership Manager is in good category (2) employee performance is in good category (3) Simple linear regression hypothesis test results is there is no positive and significant relationship between the two variables